Optimization of Guidance and Counseling by the Binmas Unit in Preventing Drug Abuse in the Jurisdiction of the Surakarta Polresta - Wibisono, Ramadhan (Advances in Police Science Research Journal, 2024)
The purpose of this study is to describe the role of the Binmas Unit with the aim of reducing drug abuse in the Surakarta Police jurisdiction. This research approach uses qualitative with the research method used is field research. The research location focuses on Surakarta Police. The data sources in this research are primary data sources by conducting interviews and secondary data sources, namely records and reports. The data analysis technique in this study uses three stages, namely data reduction, data presentation and conclusion drawing. The results of this study explain that there have been not optimized guidance and counseling activities carried out by Satbinmas Polresta Surakarta related to drug abuse. The results of the above analysis can be seen that the internal factors that can support the optimization of guidance and counseling to prevent drug abuse are the adequate quality of human resources, the availability of facilities and infrastructure and the high ’market’ (community) attention to the guidance and counseling program carried out by Satbinmas.